PENDIDIKAN ISLAM MULTIKULTURAL DALAM INDIKATOR MODERASI BERAGAMA DI INDONESIA - Athoillah Islamy (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
The mainstreaming of religious moderation in Indonesia is not always warmly welcomed, because there are still those who consider it a liberalization or secularization of religion. This study seeks to identify the value of multicultural Islamic education in the indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia. This literature research uses a normative-philosophical approach. The analytical theory used is the values of multicultural Islamic education formulated by Azyumardi Azra. The results of the study conclude that there are dimensions of the value of multicultural Islamic education in the four indicators of religious moderation in Indonesia. First, the value of tasamuh education on indicators of tolerance in the formation of Islamic religious social understanding and attitudes that respect the reality of the plurality of life among religious communities. Second, the value of peace education on indicators of national commitment in the formation of Islamic religious understanding and social attitudes that emphasize peace and unity in state life. Third, the value of humanism education on anti-radicalism indicators in the formation of Islamic religious social understanding and attitudes that uphold human values. Fourth, the value of wasatiyah education on accommodative indicators of local culture in the formation of moderate Islamic religious understanding and social attitudes to address the plurality of local traditions as long as they do not conflict with Islamic teachings. The theoretical implication of this research is that there is relevance of universal values in indicators of religious moderation in Indonesia with various values of multicultural Islamic education.